PENGARUH MOTIVASI, KEPEMIMPINAN, KEPUASAAN KERJA DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PT. TASPEN (PERSERO) KANTOR CABANG UTAMA, SEMARANG - Fitria Eka Putri Rizqi, 10.05.51.0072; Waruwu, Penunjang (Students Journal of Economic and Management, 2014)
This study analyzed the influence of Motivation, Leadership, Job Satisfaction and Career Development on Employee Performance. Object of study in this paper is PT. TASPEN Kantor Cabang Utama Semarang. Making populations in this study is the use census study was 60 respondents to the method of data collection using questionnaires (questionnaire) by distributing a list of statements to the respondents in order to obtain information. The purpose of the study was formulated to seek answers to the flow that affect employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of the instrument, regression analysis, to test the effect of partially magnitude of each independent variable were tested by regression analysis. The results of the research are: (1) Motivation has a positive and significant impact on employee performance. (2) Leadership has a positive and significant impact on employee performance. (3) Job Satisfaction has a positive and significant impact on employee performance. (4) Career Development has a negative and significant impact on employee performance.Keywords: Motivation, Leadership, Job Satisfaction, Career Development and Employee Performance